Attainment of treat-to-target endpoints in SLE patients with high disease activity in the atacicept phase 2b ADDRESS II study. (27th February 2020) - Morand, Eric F; Isenberg, David A; Wallace, Daniel J; Kao, Amy H; Vazquez-Mateo, Cristina; Chang, Peter; Pudota, Kishore; Aranow, Cynthia; Merrill, Joan T
Abstract: Objective: Low disease activity (LDA) and remission are emerging treat-to-target (T2T) endpoints in SLE. However, the rates at which these endpoints are met in patients with high disease activity (HDA) are unknown. Atacicept, which targets B lymphocyte stimulator and a proliferation-inducing ligand, improved disease outcomes in SLE patients with HDA (SLEDAI-2K ≥10) at baseline in the phase 2b ADDRESS II study. This is a post hoc analysis of T2T endpoints in these patients. Methods: Patients received weekly atacicept (75 or 150 mg s.c.) or placebo for 24 weeks (1:1:1 randomization). Attainment of three T2T endpoints, LDA (SLEDAI-2K ≤ 2), Lupus Low Disease Activity State (LLDAS) and remission (clinical SLEDAI-2K = 0, prednisone-equivalent ≤5mg/day and Physician's Global Assessment <0.5), was assessed and compared with SLE Responder Index (SRI)-4 and SRI-6 response. Results: Of 306 randomized patients, 158 (51.6%) had baseline HDA. At week 24, 37 (23.4%) HDA patients attained LDA, 25 (15.8%) LLDAS and 17 (10.8%) remission. Each of these endpoints was more stringent than SRI-4 ( n = 87; 55.1%) and SRI-6 ( n = 67; 42.4%). Compared with placebo ( n = 52), at week 24, patients treated with atacicept 150 mg ( n = 51) were more likely to attain LDA [odds ratio (OR) 3.82 (95% CI: 1.44, 10.15), P = 0.007], LLDAS [OR 5.03 (95% CI: 1.32, 19.06), P = 0.018] or remission [OR 3.98 (95% CI: 0.78, 20.15), P = 0.095]. Conclusion: At week 24, LDA, LLDAS and remission were more stringent than SRI-4 and SRI-6 response, were attainable in the HDA population and discriminated between treatment with atacicept 150 mg and placebo. These results suggest that T2T endpoints are robust outcome measures in SLE clinical trials and support further evaluation of atacicept in SLE. Trail registration: ClinicalTrials.gov, http://clinicaltrials.gov, NCT01972568.